2017
DOI: 10.1111/prd.12198
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and the special needs patient

Abstract: Individuals with special needs are at more risk of dental disease, including periodontal diseases, and have a greater prevalence and incidence of periodontal diseases than the rest of the population. Genetic or medical conditions, and/or the use of prescription medication or recreational substances, may further increase the risk for susceptibility to periodontal disease. The success of preventing or controlling periodontal diseases amongst this group of patients has not been established. Even those individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…The wide variation in caries experiences might be due to several factors like race, geographical locations, cultural and ethnic differences (Olatosi, Inem, Sofola, Prakash, & Sote, ). Moreover, the existing evidence supported that individuals with SHCN had high levels of dental plaque, as well as high incidence and severity of periodontal diseases (Brown et al., ; Gandhi & Klein, ; Zhou et al., ). A cross‐sectional study reported that above 90% of children with SHCN presented with gingival bleeding or had supra‐ or sub‐gingival calculus (Fakroon, Arheiam, & Omar, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The wide variation in caries experiences might be due to several factors like race, geographical locations, cultural and ethnic differences (Olatosi, Inem, Sofola, Prakash, & Sote, ). Moreover, the existing evidence supported that individuals with SHCN had high levels of dental plaque, as well as high incidence and severity of periodontal diseases (Brown et al., ; Gandhi & Klein, ; Zhou et al., ). A cross‐sectional study reported that above 90% of children with SHCN presented with gingival bleeding or had supra‐ or sub‐gingival calculus (Fakroon, Arheiam, & Omar, ).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies also further revealed that individual with SHCN had an increased risk of poor oral health (Brown, Ford, & Symons, ; Gandhi & Klein, ; Nqcobo, Yengopal, Rudolph, Thekiso, & Joosab, ; Zhou, Wong, Wen, & Mcgrath, ), limited studies had been conducted among young children with SHCN to explore the covariates which were associated with their oral health status. The aims of this study were to determine the oral health status among preschool children with SHCN, and explore the factors which had a potential impact on their oral health status.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with special needs are at higher risk of dental disease, including periodontal diseases, and special needs patients have a greater prevalence and incidence of periodontal diseases compared with the rest of the population . Genetic or medical conditions, and/or the use of prescription medication or recreational substances, may further increase the risk for susceptibility to periodontal disease.…”
mentioning
confidence: 99%
“…This study found that a lower level of education (up to elementary school) and severe stress were significant risk factors for PD in rural areas. Many previous studies have also found that the risk of PD is inversely correlated with the level of education, and that stress and psychological factors such as depression, anxiety, and emotional and work stress are potential risk indicators or risk factors for PD . Excessive stress not only exerts an indirect negative effect when combined with smoking and alcohol intake, but also reportedly leads directly to physiological changes in the periodontium .…”
Section: Discussionmentioning
confidence: 98%